Malaysia MDF industry: the raw material scenario / Zulhelmi Mohd Ali - Mohd Ali, Zulhelmi (2001)
Malaysia is one of the world's producers of medium density fiberboard (MDF) productions. At present, there are 10 MDF factories in operation. They use rubberwood and hardwood residues as their raw material for MDF production. This show that rubberwood is widely use as raw material for MDF. However, the supplies of this rubberwood in the coming years are not enough. We have to find another alternative raw material to replacing the rubberwood. Thus, we can use oil palm trunk. as a new raw material for MDF.